Finnish pre-service teachers' understandings of the role of language(s) in learning mathematics - Alisaari Jenni; Heikkola Leena M; Harju-Autti Raisa (Taylor & Francis, 2025)
We examined Finnish pre-service primary school teachers' understandings of the role of language(s) in learning mathematics and how these understandings developed during a period of teaching practice. We also examined how the participants experienced the usefulness of the ready-made multilingual digital material Binogi and how the teaching practice period influenced their thoughts on multilingual pedagogies. Our results indicate that the teacher training period increased awareness of linguistic challenges and of the importance of students' L1s in learning. However, some participants' views reflected monolingual ideologies, especially regarding the conditional use of L1s. Regarding linguistic support, the participants reported using visual supports and explaining vocabulary and structures. Although many participants perceived Binogi as beneficial and motivating, less than half used it. Some participants emphasised that the practice period reinforced their understanding of the importance of multilingual pedagogies. It is important to critically reflect on the language policies and practices of Finnish teacher education and support the dialogue between research and practice regarding a shared understanding of valuing linguistic diversity in teacher education.